Influence of Sensory Properties in Moderating Eating Behaviors and Food Intake - Forde, Ciarán G.; de Graaf, Kees (Frontiers in Nutrition, 2022)
Sensory properties inform likes and dislikes, but also play an important functional role in guiding food choice and intake behaviour. Odors direct food choice and stimulate sensory-specific appetites and taste helps to anticipate calorie and nutrient content of food. Food textures moderate eating rate and the energy consumed to satiation and post-ingestive metabolism. We summarize how sensory cues moderate intake, and highlight opportunities to apply sensory approaches to improve dietary behaviour. Salt, sweet and savory taste influence liking, but also influence energy intake to fullness, with higher taste intensity and duration linked to lower intake. Psycho-physical studies show it is relatively easy to rank taste intensities at different concentrations but more challenging to discriminate fat contents, and fat discrimination declines further when combined with high-taste intensity. Fat has low impact on sensory intensity, but makes significant contributions to energy content. Combinations of high taste and fat-content can promote passive energy over-consumption, and adding fat also increases energy intake rate (kcals/min), reducing opportunities to orally meter consumption. Consumers adapt their oral processing behaviors to a foods texture, which can influence the rate and extent of energy intake. Understanding how texture influences eating behaviors and bolus formation, affords new opportunities to impact eating rate, energy intake and metabolic response to food. Food formulation has traditionally focused on composition and sensory appeal. Future research needs to consider the role of sensory properties in moderating consumer interaction with their food environment, and how they influence calorie selection, and shape our eating behaviors and intake.